Analgesic effect of S (+)‐flurbiprofen plaster in a rat model of knee arthritis: analysis of gait and synovial fluid prostaglandin E2 levels. (1st April 2018) - Fukumoto, Ayaka; Tajima, Kyoko; Hori, Miyuki; Toda, Yoshihisa; Kaku, Shinsuke; Matsumoto, Hideo
Abstract: Objectives: We developed S (+)‐flurbiprofen plaster (SFPP), a novel NSAID patch containing S (+)‐flurbiprofen (SFP), a potent cyclooxygenase (COX) inhibitor. The purpose of this study was to assess efficacy of SFPP by analysing its effect on the gait disturbance and measuring the prostaglandin E2 (PGE2 ) production in synovial fluid in a rat model of knee arthritis. Methods: Knee inflammation was induced in rats by intra‐articular injection of a yeast suspension. Subsequently, an NSAID patch containing SFP, ketoprofen or loxoprofen was applied over the affected knee. Gait was assessed at 2, 4 and 6 h after application of the patch. The PGE2 concentration in the synovial fluid was measured after the gait assessment. Key findings: Application of SFPP (0.125, 0.25, 0.5 or 1 mg/sheet) was followed by a decrease in the visual gait score at all the doses examined. In the case of the other two NSAID patches, only the ketoprofen patch (1 or 2 mg/sheet) and loxoprofen patch (5 mg/sheet) produced a decrease in the visual gait score. All of the NSAID patches decreased the PGE2 production in the synovial fluid. Conclusions: These results suggest the potential usefulness of SFPP as an analgesic patch in patients with inflammatory joint pain.